Effectiveness of current protection for Maui dolphin - Slooten, Elisabeth (J. Cetacean Res. Manage., 2020)
This paper describes changes to protected areas for Maui dolphin implemented in 2012 and 2013 and estimates their effectiveness in reducing bycatch. An Expert Panel of New Zealand and international scientists, convened by the New Zealand government in 2012, estimated that five Maui dolphins were killed in fishing gear each year – one in trawl fisheries and four in gillnet fisheries. The estimated number of trawl mortalities is unchanged, as no additional protection from trawling has been implemented. The number of gillnet mortalities per year is estimated to have decreased to at best two per year.